2004
DOI: 10.1002/dvdy.20231
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of RAR‐responsive genes in the Xenopus neurula using cDNA microarrays

Abstract: Retinoid signaling is important for patterning the vertebrate hindbrain and midaxial regions. We recently showed that signaling through retinoic acid receptors (RARs) is essential for anteroposterior patterning along the entire body axis. To further investigate the mechanisms through which RARs act, we used microarray analysis to investigate the effects of modulating RAR activity on target gene expression. We identified 334 up-regulated genes (92% of which were validated), including known RA-responsive genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 108 publications
0
47
0
Order By: Relevance
“…Treatment with the pan-RAR inverse agonist AGN193109 increased the expression of genes involved in patterning anterior neural structures, whereas treatment with pan-RAR agonist TTNPB decreased the expression of anterior marker and cement glandspecific genes (Koide et al, 2001), revealing a set of genes specifically upregulated/downregulated by TTNPB (Arima et al, 2005). Validation studies identified a subset upregulated by AGN193109.…”
Section: Resultsmentioning
confidence: 94%
“…Treatment with the pan-RAR inverse agonist AGN193109 increased the expression of genes involved in patterning anterior neural structures, whereas treatment with pan-RAR agonist TTNPB decreased the expression of anterior marker and cement glandspecific genes (Koide et al, 2001), revealing a set of genes specifically upregulated/downregulated by TTNPB (Arima et al, 2005). Validation studies identified a subset upregulated by AGN193109.…”
Section: Resultsmentioning
confidence: 94%
“…Erf was upregulated by increased RA signaling in neurula embryos (Arima et al, 2005). Here, we show that morpholino oligonucleotide (MO)-mediated knockdown of Erf or Etv3 results in loss of primary neurons accompanied by paralysis, phenocopying RAR loss of function.…”
Section: Introductionmentioning
confidence: 83%
“…We have previously shown that some Ets genes were responsive to changes in RAR signaling in Xenopus embryos (Arima et al, 2005). Erf was upregulated by increased RA signaling in neurula embryos (Arima et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…HoxA1-null ES cells are refractory to treatment with RA as measured by reduced expression of post-mitotic neuron markers (e.g., b-tubulin III, Nestin); RA sensitivity can be restored by rescue with HoxA1 cDNA [173]. Btg2 is also a putative direct target of RAR [174] and is induced by RA in neurula-stage embryos [175,176] and in various cell lines [174,177]. Btg2 decreases arginine methylation and lysine acetylation of histone H4 at RAR target genes, thus increasing the transcriptional activity of RAR [177].…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…Multiple genomics-based studies have elucidated some genes that respond to RA under a variety of differentiation conditions [175,176,[190][191][192][193][194][195][196]. A subset of the genes identified in these analyses will be candidate neurogenic genes regulated by RAR.…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%